Penggunaan Metode Particle Swarm Optimization (PSO) pada Optimasi Multirespon Gaya Tekan dan Momen Torsi Penggurdian Material Komposit Glass Fiber Reinforce Polymer (GFRP) yang ditumpuk dengan Material Stainless Steel (SS) - Angga Sateria; Indra Dwi Saputra; Yuli Dharta (Manutech : Jurnal Teknologi Manufaktur, 2018)
The Particle Swarm Optimization (PSO) method is one of the methods used for multirespon optimization in the manufacturing process. In this research, the material used is Glass fiber reinforced polymer (GFRP) composite material which is stacked with stainless steel material. The machining process used is a drilling process conducted on a vertical CNC machine Brother TC-22A-O. The thrust force and torque is the response used to evaluate the performance of the drilling process. The quality characteristics of this response "the smaller the better". The aim of this study was to identify the combination of process parameters to achieve the performance characteristics required in drilling process the GFRP-SS material using Particle Swarm Optimization methode (PSO). The three process parameters i.e. point angle, spindle speed, and feeding speed is used as a process parameter. Point angle was set at two different levels, while the other two were set at three different levels. Therefore, the 2 x 3 x 3 factorial is used as the experimental design. The experiments were replicated two times. The minimum thrust force and torque could be obtained by using point angle, spindle speed, and feeding speed are 118o, 2330 rpm, and 65 mm/minrespectively.